Respiratory and circulatory insufficiency during emergent long-distance critical care interhospital transports to tertiary care in a sparsely populated region: a retrospective analysis of late mortality risk. Issue 2 (15th February 2022) - Fredriksson Sundbom, Marcus; Sangfelt, Amalia; Lindgren, Emma; Nyström, Helena; Johansson, Göran; Brändström, Helge; Haney, Michael
Abstract : Objectives: To test if impaired oxygenation or major haemodynamic instability at the time of emergency intensive care transport, from a smaller admitting hospital to a tertiary care centre, are predictors of long-term mortality. Design: Retrospective observational study. Impaired oxygenation was defined as oxyhaemoglobin %–inspired oxygen fraction ratio (S/F ratio)<100. Major haemodynamic instability was defined as a need for treatment with norepinephrine infusion to sustain mean arterial pressure (MAP) at or above 60 mm Hg or having a mean MAP <60. Logistic regression was used to assess mortality risk with impaired oxygenation or major haemodynamic instability. Setting: Sparsely populated Northern Sweden. A fixed-wing interhospital air ambulance system for critical care serving 900 000 inhabitants. Participants: Intensive care cases transported in fixed-wing air ambulance from outlying hospitals to a regional tertiary care centre during 2000–2016 for adults (16 years old or older). 2142 cases were included. Primary and secondary outcome measures: All-cause mortality at 3 months after transport was the primary outcome, and secondary outcomes were all-cause mortality at 1 and 7 days, 1, 6 and 12 months. Results: S/F ratio <100 was associated with increased mortality risk compared with S/F>300 at all time-points, with adjusted OR 6.3 (2.5 to 15.5, p<0.001) at 3 months. Major haemodynamic instability during intensive care unit (ICU) transport was associated with increased adjusted OR of all-cause mortality at 3 months with OR 2.5 (1.8 to 3.5, p<0.001). Conclusion: Major impairment of oxygenation and/or major haemodynamic instability at the time of ICU transport to get to urgent tertiary intervention is strongly associated with increased mortality risk at 3 months in this cohort. These findings support the conclusion that these conditions are markers for many fold increase in risk for death notable already at 3 months after transport for patients with these conditions.